The Existence of Women’s Representation in the House of Representatives in 2019-2024 - Sapitri, Imelda; Alkadafi, Muammar; Rizal, Yose (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Indonesia as a democratic country must involve the participation of all components of society in determining the direction and policies of the country. The female voter population of 96,572,045 is greater than the male voter population of 96,294,209. The author conducted normative legal research on the existence of women's representation in DPR. As for the research results, the urgency for gender equality is: 1. Women's freedom from the patriarchal system; 2. Women can determine their future direction and goals; 3. Women as Role Models; d. Women are able to compete. The presence of women parliament can successfully change the culture from a masculine to a more female-friendly one. Regulations on women's candidacy arestated in Article 246 of the Election Law and Article 3 of PKPU No. 20 of 2018. Currently, women's representation in the DPR is 20.87%. Women's representation has succeeded in accommodating women's rights in the form of Law No. 12 of 2022 concerning Crime of Sexual Violence. An obstacle to increasing women's representation is that political parties still tend to place the serial number positions of female legislative candidates at the bottom of the serial number. With this, political parties must also consider the potential of female legislative candidates to get the leading number